Revisión sistemática de la literatura sobre sistemas adhesivos de quinta generación vs octava generación y su fuerza de adhesión (2023)
Adhesive systems are constantly updated to achieve a precise and high performance work, they are responsible for the bonding of the restorative material to the tooth surface, thus achieving day by day a great pleasure in patients to solve both functional and esthetic problems.